DEVELOPMENT OF EDUCATIONAL CONGKLAK GAME MEDIA IN GROUP GUIDANCE SERVICES TO DEVELOP POSITIVE THINKING IN STUDENTS (International Journal of Cultural and Social Science, 2026)
This study aims to develop an educational congklak game media for group guidance services to foster students’ positive thinking. This research employed the Research and Development (R&D) method using the 4D model, which includes define, design, develop, and disseminate stages. The subjects involved were one material expert, one media expert, one counseling teacher, and eight seventh-grade students at SMPN 24 Medan. Data collection techniques included material expert validation questionnaires, media expert validation questionnaires, counseling teacher response questionnaires, and student response questionnaires. Data were analyzed using descriptive quantitative analysis by calculating product feasibility percentages. The results showed that the material expert validation score was 95% and media expert validation was 86%, both categorized as very feasible. The counseling teacher response score was 86%, while student responses reached 89.75%, both categorized as strongly agree. Based on these findings, the developed educational congklak game media is considered feasible, practical, and suitable for use in group guidance services to support students’ positive thinking.